2021
DOI: 10.3390/ijms22041768
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Gene Expression of Entire Male, Immunocastrated and Surgically Castrated Pigs

Abstract: Differences in adipose tissue deposition and properties between pig male sex categories, i.e., entire males (EM), immunocastrates (IC) and surgical castrates (SC) are relatively well-characterized, whereas the underlying molecular mechanisms are still not fully understood. To gain knowledge about the genetic regulation of the differences in adipose tissue deposition, two different approaches were used: RNA-sequencing and candidate gene expression by quantitative PCR. A total of 83 differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
3
6
0
Order By: Relevance
“…Functional enrichment analysis showed that these genes were signi cantly enriched in AGE-RAGE signaling pathway in diabetic complications, Relaxin signaling pathway, Extracellular matrix (ECM) organization, Extracellular structure organization, ECM, Collagen-containing ECM, Collagen binding and ECM binding. The result was very similar to that from the study of Poklukar et al [30], and their ndings showed that the upregulated genes in entire males as compared with immunocastrated males and surgical castrates were signi cantly enriched in extracellular region/matrix (ECM) cellular components, ECM receptor interaction and focal adhesion pathways. Some genes responsible for the differences in backfat deposition between the three male sex categories were identi ed including COL1A2, COL6A3, POSTN, P4HA3, DCN, FMOD, MMP2 and MMP27 [30].…”
Section: Hub Genes In the Purple Modulesupporting
confidence: 88%
See 4 more Smart Citations
“…Functional enrichment analysis showed that these genes were signi cantly enriched in AGE-RAGE signaling pathway in diabetic complications, Relaxin signaling pathway, Extracellular matrix (ECM) organization, Extracellular structure organization, ECM, Collagen-containing ECM, Collagen binding and ECM binding. The result was very similar to that from the study of Poklukar et al [30], and their ndings showed that the upregulated genes in entire males as compared with immunocastrated males and surgical castrates were signi cantly enriched in extracellular region/matrix (ECM) cellular components, ECM receptor interaction and focal adhesion pathways. Some genes responsible for the differences in backfat deposition between the three male sex categories were identi ed including COL1A2, COL6A3, POSTN, P4HA3, DCN, FMOD, MMP2 and MMP27 [30].…”
Section: Hub Genes In the Purple Modulesupporting
confidence: 88%
“…The result was very similar to that from the study of Poklukar et al [30], and their ndings showed that the upregulated genes in entire males as compared with immunocastrated males and surgical castrates were signi cantly enriched in extracellular region/matrix (ECM) cellular components, ECM receptor interaction and focal adhesion pathways. Some genes responsible for the differences in backfat deposition between the three male sex categories were identi ed including COL1A2, COL6A3, POSTN, P4HA3, DCN, FMOD, MMP2 and MMP27 [30]. In our study, COL1A2 gene was identi ed to have the highest degree in the PPI network, which indicated that the gene was at the core of the network.…”
Section: Hub Genes In the Purple Modulesupporting
confidence: 88%
See 3 more Smart Citations